Orally administrable film containing poorly water-soluble active ingredient and preparation thereof

By homogenizing an aqueous alginate solution with a poorly water-soluble bioactive material and an emulsifier, the method overcomes the challenge of incorporating high amounts of such materials into mucoadhesive films, resulting in stable and effective bioactive delivery.

JP7664916B2Active Publication Date: 2025-04-18BIOTA LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022525669
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-04
Filing Date
2020-11-02
Publication Date
2025-04-18
Estimated Expiration
2040-11-02

AI Technical Summary

Technical Problem

Existing mucoadhesive films struggle to incorporate poorly water-soluble bioactive materials in high amounts due to solubility issues and phase separation tendencies, leading to instability and poor bioavailability.

Method used

The method involves homogenizing an aqueous alginate solution with a poorly water-soluble bioactive material and an emulsifier, achieving a high weight ratio of bioactive compound to alginate, which allows for the production of stable and uniform mucoadhesive films.

Benefits of technology

This approach enables the creation of mucoadhesive films with high bioactive material content that are chemically stable, uniform, and processable, ensuring effective mucosal adhesion and prolonged oral residence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664916000001
    Figure 0007664916000001
  • Figure 0007664916000002
    Figure 0007664916000002
  • Figure 0007664916000003
    Figure 0007664916000003
Patent Text Reader

Abstract

The present invention discloses an orally administrable mucoadhesive film composition containing a high loading of a poorly water-soluble bioactive material, alginate as the primary film-forming polymer, and an emulsifier. A method for preparing such a film is also provided, which comprises homogenizing a precursor composition containing these ingredients.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to orally administrable mucoadhesive films based on alginate polymers containing high loadings of poorly water-soluble bioactive materials and methods for their production. [Background technology]

[0002] Oral administration of bioactive substances is commonly used in the fields of pharmaceuticals, oral care products, and dietary supplements. There are many bioactive materials. These materials or substances, called active pharmaceutical ingredients (APIs) in the pharmaceutical industry, are incorporated into products such as dietary supplements, oral care products, and pharmaceuticals to promote health, prevent disease, or provide other benefits to the well-being of the individual.

[0003] Conventionally, bioactive substances are administered as products in various dosage forms such as syrups, tablets, capsules, etc., but it is also known to use polymer films, such as oral disintegrating films and mucoadhesive films, to deliver bioactive materials. Products containing bioactive substances usually stabilize the substances both physically and chemically.

[0004] Orally administrable mucoadhesive films are delivery systems that incorporate active agents into a polymeric matrix that adheres to the oral mucosa. When the film is placed in the oral cavity and hydrated by saliva, the bioactive agents incorporated within the film are released from the matrix via diffusion and / or by erosion / disintegration or dissolution of the matrix containing the bioactive material. Bioactive materials released from the matrix may be removed from the oral cavity by swallowing, but may also be absorbed through the mucosa in the oral cavity, thereby bypassing the hepatic clearance system.

[0005] It is known that the clinical efficacy of oral dosage forms of poorly water-soluble substances such as coenzyme Q10 (CoQ10) and lutein is often limited due to the low bioavailability of such bioactive substances (Sato, et. al., Biol. Pharm. Bull.36(12)2012-2017(2013)).

[0006] CoQ10, also known as ubiquinol or ubidecarenone, is a 1,4-benzoquinone, where Q represents a quinone chemical group and 10 represents the number of isoprenyl chemical subunits in the decaisoprenyl radical, i.e., its "tail". CoQ10 is a lipophilic vitamin-like fat-soluble substance present in all respiring eukaryotic cells. CoQ10 is a yellow or orange solid with a melting point of 48°C to 52°C. CoQ10 is abundant in products sold as dietary supplements, as low CoQ10 concentrations in subjects have been found to be associated with several conditions, including cardiovascular disease, neurological disease, muscular dystrophy, and periodontal disease. CoQ10 is practically insoluble in water due to its size and structure, and exhibits very low water solubility, e.g., 2-3 parts per million (ppm) (i.e., 2-3 mg / L). The most commonly used methodology for CoQ10 delivery systems today involves gel capsules containing CoQ10. Many currently known CoQ10 products are formulated as swallowed softgel capsules sold with recommended daily doses of 60-400 mg or more. Problems with consumer adherence to conventional CoQ10 softgels and similar swallowed products are described in U.S. Pat. No. 9,775,332.

[0007] To overcome the limitations of oral dosage forms of poorly soluble active materials, various delivery strategies are known in the art including, for example, micronized particles, nanoparticulate systems, polymer inclusion complexes, gelation to incorporate the active material in a dissolved state into soft gel capsules, powder amorphization, etc., to increase the surface area and improve the dissolution rate of the active material, among others.

[0008] Another approach to improve the administration of poorly bioavailable active materials is through mucoadhesive films. A common component that enables mucoadhesion is an alginate-based material. Alginate is a natural polysaccharide that contains negatively charged guluronic and mannuronate structural units, which can be arranged randomly, in blocks, or in alternating fashion. Alginate belongs to a group of materials that are generally recognized as safe (GRAS) by regulatory authorities. The use of alginate to produce oral mucoadhesive films, including blending alginate with other natural or synthetic polymers, has been described in several previous publications. For example, US Patent No. 8,840,935 provides details regarding the characteristics of such films, including the viscosity grade of alginate, film thickness, oral residence time, organoleptic properties, mechanical properties, challenges associated with the film preparation process, etc. Further details regarding oral film properties related to mucoadhesion and oral residence time are disclosed in US Patent No. 1,028,5910.

[0009] A film containing CoQ10 and alginate is also shown in JP 2018-203618. In this publication, the film was made using a relatively high concentration of the film-forming emulsifier starch octenyl succinate (with a ratio of active ingredient up to 1:1). The publication discloses and illustrates a two-step process of forming a CoQ10-succinylated starch aqueous emulsion by high shear homogenization and mixing the formed emulsion with an alginate solution to obtain a casting mass into a film. Also, US Pat. No. 9,655,849 discloses an improvement in the bioavailability and / or solubility of coenzyme Q10, and discloses providing a method for preparing a particulate composition containing coenzyme Q10, which includes dispersing and / or dissolving coenzyme Q10 in a suitable solvent and combining the coenzyme Q10 mixture with an encapsulating agent. Additionally, U.S. Patent Application Publication No. 2019 / 0269649 discloses liposomes and specialty formulations aimed at solving the problem of incorporating oily plant extracts into oral film strips, noting that direct incorporation of such oily extracts typically results in a sticky mixture that does not form a processable film having desirable properties such as dry to the touch, easy to handle and package, and / or easy to consume.

[0010] Incorporating poorly water-soluble materials into hydrophilic matrices is generally not a simple task. The challenge stems from the fact that the concentration of such bioactive substances may be limited by forced intimacy with the hydrophilic polymer matrix. Moreover, the incorporation of lipophilic substances into hydrophilic matrices, especially solid matrices, requires the use of large amounts of emulsifiers and / or solubilizers to maintain the thermodynamic stability of the film and prevent the lipophilic substances from blooming (i.e., leaking) from the matrix. The concentration of emulsifiers in the matrix usually depends on its type and can even be twice the concentration of the bioactive material present in said film. Thus, the loading amount of poorly soluble substances into hydrophilic matrices is rather limited. This limitation is more pronounced, for example, during the preparation process of the composition (separation of oil-in-water emulsion) and during the storage period of the resulting film, when the active material, which may be in the form of an oily liquid, is processed in large quantities into a matrix with hydrophilic polymers due to the tendency for phase separation. For example, US Patent No. 8,758,803 discloses a film-like preparation that disintegrates rapidly upon contact with saliva or other aqueous liquids and can stably contain large amounts of at least one oily substance. It is noteworthy that the incorporated oily substance was found to leach out from the film prepared with alginate.

[0011] Similarly, U.S. Pat. No. 8,759,282 discloses films of soluble APIs in selected alginates or APIs with pH-sensitive solubility that are sparingly soluble in deionized water, such as ibuprofen (21 mg / L at 20° C.), without the use of emulsifiers.

[0012] Additionally, PCT International Publication WO2019 / 219773 discloses alginate films with similar cannabinoids, e.g., 5-20 mg of cannabidiol (CBD) per dosage unit as described therein. CBD has a water solubility of 12.6 mg / L, so CBD is considered to be a poorly water-soluble or lipophilic drug. CBD is incorporated into the alginate film in large amounts of surfactant / emulsion bases, organic cosolvents, or at a pH above 12 where CBD is water-soluble.

[0013] There is a need in the art to provide a mucoadhesive film that contains a sufficiently high loading of poorly soluble bioactive ingredients.Specifically, there is a need to provide a mucoadhesive film of high loading of natural bioactive ingredients, such as CoQ10, that is composed only of natural ingredients.The film should be sufficiently uniform, crack-free, preferably chemically stable, easily manufactured, adhere to and present on the oral mucosa, not show exudation, have a good palatability, and have an acceptable long shelf life. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] U.S. Patent No. 9,775,332 [Patent Document 2] U.S. Patent No. 8,840,935 [Patent Document 3] U.S. Patent No. 10285910 [Patent Document 4] Japanese Patent Publication No. 2018-203618 [Patent Document 5] U.S. Patent No. 9,655,849 [Patent Document 6] US Patent Application Publication No. 2019 / 0269649 [Patent Document 7] U.S. Patent No. 8,758,803 [Patent Document 8] U.S. Patent No. 8,759,282 [Patent Document 9] International Publication No. 2019 / 219773 Summary of the Invention [Means for solving the problem]

[0015] In some embodiments, the present invention provides mucoadhesive, orally administrable alginate films that contain a high loading of at least one poorly soluble bioactive material. Such mucoadhesive films are typically difficult to achieve. The active material has low water solubility and cannot be readily dissolved with the film former.

[0016] It has now been unexpectedly discovered that films of acceptable quality can be obtained by homogenizing a dispersion of poorly soluble bioactive material in an aqueous solution of alginate (e.g., as opposed to the conventional method of homogenizing the active agent at low viscosity and then adding a solution of a film-forming polymer). According to one aspect, provided herein is a method for producing a mucoadhesive film having a high loading of poorly water-soluble bioactive compound. The mucoadhesive film comprises at least one alginate as the primary film-forming polymer, as detailed in more detail below. The method comprises homogenizing an aqueous solution of alginate with a poorly water-soluble bioactive material and an emulsifier to provide a mass suitable for casting. Homogenization is achieved at a high weight ratio of bioactive compound to alginate, for example, in the range of 1:2.5-2.5:1, 1:2-2.5:1, or 1:1-2.5:1. The homogenization step provides a mass suitable for casting, which can be further processed into a film by casting, drying, etc.

[0017] Preferably, the poorly water soluble bioactive material can be combined with an emulsifier prior to the homogenization step, and the resulting mixture can then be combined with the alginate solution.

[0018] Alternatively, the alginate solution can be combined with an emulsifier prior to the homogenization step and the resulting mixture can then be combined with the poorly water soluble bioactive material.

[0019] Also, prior to the homogenization step, the poorly water-soluble bioactive material may be mixed in molten form with an emulsifier, for example when the active agent is CoQ10, and the resulting mixture may be combined with an adsorbent powder, or the resulting mixture may be further milled and then combined with an alginate solution.

[0020] The homogenized mixture, i.e., a castable mass, can be cast onto a suitable liner, particularly at wet film thicknesses greater than 1 mm, for example in the range of 1-3 mm. Casting is preferably carried out using a slit die apparatus at any suitable temperature, but may be carried out at a temperature between 50° C. and 85° C.

[0021] According to a further aspect, there is provided herein an orally administrable mucoadhesive film obtainable by a process essentially as described herein.

[0022] Further provided herein is an orally administrable mucoadhesive film comprising at least one poorly water-soluble bioactive material, an emulsifier, and alginate. Alginate is the predominant film-forming polymer in the film. The film is characterized in that the high loading of poorly water-soluble bioactive material in the film is between 10% and 50% by weight, such as between 15% and 45% by weight, such as between 20% and 30% by weight, of the dry weight of the film. Alternatively or additionally, the high loading of poorly water-soluble bioactive material is such that the dosage is between 20 mg per square centimeter of film and the thickness of the dry film varies in the range of 50 to 600 μm, preferably 100 to 400 μm.

[0023] In general, in the orally administrable mucoadhesive film according to some preferred embodiments of the present invention, the film contains at least one poorly water-soluble bioactive material, at least one emulsifier, and alginate as the main film-forming polymer, and the weight ratio between the bioactive material and the alginate is about 1:2.5 to about 2.5:1, preferably between 1:2 and 2.5:1, for example between 1:1 and 2.5:1. The concentration of the emulsifier is usually less than 1 / 5 of the concentration of the poorly water-soluble bioactive material, for example between 1 / 10 and 1 / 100, preferably between 1 / 50 and 1 / 60. The emulsifier can be selected from the group consisting of phospholipids, sorbitan fatty acid esters, ethoxylated sorbitan esters, ethoxylated fatty acid esters or fatty alcohol ethers, sucrose fatty acid esters, and combinations thereof. The emulsifier is preferably a phospholipid, for example lecithin.

[0024] According to a preferred embodiment of the present invention, the poorly water-soluble bioactive material typically has a water solubility of less than 10 mg / L at 20°C, for example, between 0.1 and 8 mg / L, or between 1 and 5 mg / L at 20°C, and may be substantially insoluble in the film, as described in more detail below. The poorly water-soluble bioactive material is typically selected from the group consisting of vitamins and vitamin-like substances naturally occurring in the human body, carotenes, terpenes, flavonoids, cannabinoids, natural oils, and plant extracts. In some preferred embodiments, the poorly water-soluble bioactive material is coenzyme Q10, preferably at a concentration of between 10 and 50% by weight, for example between 15% and 45% by weight, based on the dry weight of the film. In some particularly preferred embodiments, the film comprises coenzyme Q10, alginate, and lecithin. The mucoadhesive film may contain 10-45% by weight of the dry weight of the film of alginate (e.g., 25-45% by weight), 10-50% by weight of the dry weight of the film of coenzyme Q10 (e.g., 15-45% by weight, more specifically, 15-25% by weight), and 0.01-5.0% by weight of the dry weight of the film of lecithin (e.g., 0.05-0.2% by weight). The film may also further contain one or more film-forming polymers other than alginate, plasticizers, flavorings and / or fillers, up to 100% by weight of the formulation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Generally, the films are dry polymer compositions formed by polymeric matrix formers (i.e., film formers), as described in more detail below, and contain additional components such as, inter alia, plasticizers, taste masking agents, and bioactive materials dissolved or dispersed in the film. These films are usually produced by preparing a solution of a film-forming polymer (some polymers may be cast from a dispersant at a temperature to fuse the particles into a film, forming a so-called latex-type film; alginate films are usually produced from a solution) and dissolving or dispersing additional components therein to provide a precursor composition suitable for casting, i.e., a casting solution, sometimes called a "wet film" (cast on a liner but not dried), or a "casting solution," "active mass," or a "mass suitable for casting" or "mass," as used interchangeably herein. The casting solution contains all the components of the film in the required ratios (and as defined below in the context of the present invention) along with the solvent that evaporates during drying of the film. As such, it typically has a dry film composition with a ratio between the components as described in greater detail below, and further comprises a solvent, e.g., an essentially aqueous medium, which (apart from residual moisture) is finally evaporated during the drying step. The casting solution is then applied onto a support (i.e., a substrate such as a liner, as described below), and dried to provide the resulting, i.e., dry, film, which can be further processed, e.g., laminated, rolled, cut to shape as required, and / or filled into unit doses. The amounts of components in the composition are therefore selected to meet the requirements of these two separate aspects, i.e., the wet film and the resulting dry film.

[0026] The amount of dry film is often referred to as "dry weight", but unless otherwise stated, it is usually expressed in terms of a virtually dried film, which in practice usually contains some residual moisture. In the case of alginate films, the residual moisture content can be quite high, e.g. 5-15% by weight. Residual moisture can be easily determined by drying to constant weight at elevated temperatures, e.g. 110°C, and is often called loss on drying (LOD). The amount of each component in a composition is therefore usually given without reference to the LOD.

[0027] The term "main film-forming polymer" as used herein generally refers to alginate or a mixture of alginates, and refers to the fact that the total weight concentration of alginate in the film is higher than the total concentration of other film-forming polymers that may be included in the film. Thus, alginate forms the polymer film matrix. The ratio of alginate to all film-forming agents may also be greater than 1:1, for example, alginate may be at least 50% of all film-forming agents. Preferably, alginate is greater than 60% of the film-forming agents, more preferably greater than 70%. In some embodiments, alginate is the only film-forming agent, i.e., the film-forming composition in the film consists essentially of alginate. The film may further include additional excipients, such as plasticizers, sweeteners, preservatives, buffers, fillers (bulking agents), co-film formers, co-solvents, stabilizers, flavors, and colors.

[0028] It has now unexpectedly become apparent that films of acceptable quality and processability, i.e. uniform throughout the casting in terms of thickness and content, flexible and mechanically strong, can be obtained by homogenizing a dispersion of poorly soluble bioactive material in an alginate solution. It is common to avoid homogenizing solutions that contain large amounts of polymer and have high viscosity as a rule. Such homogenization is not usually a problem-free process, leading to overheating of the equipment, requiring fine control of mass and heat transfer in the reactor, avoiding local heating around and inside some homogenizers, and introducing a large amount of air bubbles that are poorly removed. However, when a relatively large amount of poorly soluble bioactive material is homogenized with alginate in the presence of a small amount of emulsifier, especially in the specific weight ratio of bioactive material to alginate and optionally emulsifier as generally described herein, homogenization of the mixture can result in a film of active mass suitable for casting. The air bubbles trapped in the active mass thus produced can be easily removed by standard degassing techniques. Additionally, conventional processing results in much more brittle films with cracks, which greatly reduces the useful film area that can be cut into dosage units.

[0029] The uniformity of the obtained film is of paramount importance for further processing into final dosage units. Uniformity can usually be expressed in terms of the weight change per unit area of ​​the film. The change is usually a relative standard deviation expressed as a percentage. This index is obtained by accurately weighing a unit of film normalized by area, taking the average weight and the standard deviation of the weight of the samples, and dividing the standard deviation by the mean value. Usually, the standard deviation of the average weight per standard area is less than 20%, preferably less than 15%, more preferably less than 12%, or less than 10%, or less than 8%, or less than 7%, or less than 6%, or less than 5%. Uniformity can also be expressed as the relative standard deviation of the average content of poorly water-soluble bioactive material per unit area. Additionally, uniformity can be expressed by the relative standard deviation of the average thickness of the obtained film. It is readily understood that uniformity means that the cast and dried film is typically free of powder agglomerates and covers the entire area of ​​the cast, i.e., free of segregation which is known to occur under certain conditions, e.g., due to surface tension mismatch between the active mass and the liner causing the active mass to aggregate into islands on the liner, or due to improper drying methods, etc.

[0030] The resulting film typically has sufficient flexibility and mechanical strength to withstand normal handling of the film (sometimes referred to as "processable"). Film properties include flexibility and strength. A flexible film can be easily deformed at least several times without significant breakage (cracking), and a strong film does not tear during standard handling deformations, such as removal from a substrate liner. The Examples section describes one method of assessing a film's receptivity to processing under the "fold resistance" test. A processable film with adequate flexibility and mechanical strength can be easily cut into unit dosages of the desired shape and size without cracking the cut dosage units or causing cracks to propagate through the film being cut.

[0031] The films of the present invention are mucoadhesive, i.e., they exert good adhesion and slight pressure when contacted with the oral mucosa, and as described in more detail below, the films typically exhibit acceptable oral residence times.

[0032] The method according to the present invention is characterized in that an aqueous solution of alginate containing a poorly water-soluble bioactive material is homogenized, for example in the presence of an emulsifier. When the weight ratio of poorly water-soluble bioactive material to alginate is high, for example about 1:2.5 to about 2.5:1, homogenization can be easily achieved without providing excessive means, for example for degassing, especially when the amount of emulsifier is less than 1 / 5 of the concentration of the poorly water-soluble bioactive material.

[0033] Homogenization can be carried out using various methods known in the art. Preferably, the homogenization step is carried out using a high shear mixer, such as a rotor-stator type homogenizer, an Ultra-Turrax type homogenizer, or a mechanical mixer equipped with a high shear impeller of suitable construction depending on the vessel used. The specific impeller construction and the operating speed that delivers a particular shear intensity will depend on the equipment used, but may vary depending on the viscosity and composition of the fluid, and other parameters. Typical speeds for shear type impellers can be 1000 revolutions per minute (rpm) or higher, preferably about 1500 rpm or higher, and more preferably 5000 rpm or higher. Homogenization can be carried out continuously or intermittently, at the same speed or at different speeds, such as progressively higher speeds. Without being bound by any particular theory, it is believed that the alginate stabilizes the poorly water-soluble bioactive material in the mass when there is a high amount of poorly water-soluble bioactive material, especially when there is a relatively low amount of emulsifier, and then during the drying stage and thereafter, produces a uniform and homogenous film in which the poorly water-soluble bioactive material is evenly dispersed throughout the film matrix, providing sufficient film flexibility and mechanical strength.

[0034] The degassing of the active mass aims to expel air bubbles from the solution. These air bubbles, although small in size, inevitably grow during the drying of the film due to the evaporation interface where they are present, and in view of the surrounding solidifying film components, impede the expulsion of the air bubbles from the cast wet film. These air bubbles cause weak spots, cracks that initiate and propagate, leading to large variations in weight and thickness, delamination of the film, and an overall poor film quality. Degassing is usually carried out in various ways, including the addition of antifoaming agents, centrifugation, exposure to (high) vacuum, and other techniques. However, the most common technique is the slow stirring of the solution in a closed system under very low shear rates, preferably under reduced pressure and moderately elevated temperatures, to avoid solvent losses. It has now surprisingly been found, according to the method according to the invention, that a simple degassing technique may be sufficient to release all the air bubbles trapped in a mixture of high viscous active masses.

[0035] Thus, the homogenization step is a process carried out in an essentially aqueous medium. The term "essentially aqueous medium" indicates that water, e.g., pharmaceutical or food grade deionized water, is the primary solvent of the mixture undergoing the homogenization step. The essentially aqueous medium may further contain non-aqueous liquid components such as plasticizers, oils, flavorings, organic co-solvents, etc., in an amount that is insufficient to dissolve the poorly water-soluble bioactive material, e.g., the undissolved portion of the poorly water-soluble bioactive material is more than 85% in the essentially aqueous medium, preferably more than 99%. The essentially aqueous medium usually contains 75% to 100% water by weight, preferably more than 80% water by weight, more than 85% water by weight, more than 90% water by weight, or most preferably more than 99% water by weight of the total weight of the solvent.

[0036] Thus, the homogenization step is performed on an aqueous alginate solution, a poorly water soluble bioactive material, and an emulsifier, but the mixture for the homogenization step may also contain ingredients including additional film forming polymers (with alginate being the predominant film forming polymer), plasticizers, fillers, flavorings, taste masking agents, and / or any further ingredients that may be present in the film, as described below.

[0037] The homogenization and degassing steps may each be carried out under reduced pressure. The use of reduced pressure reduces the amount of air trapped in the solution and accelerates the escape of trapped air. Usually, the appropriate reduced pressure value for the homogenization and / or degassing steps is easily determined depending on the equipment used, the temperature used, the use of a condenser, etc. Preferably, when degassing and / or homogenization is carried out under reduced pressure, the process includes the complementary cooling and condensation of the vapors of the alginate solution or homogenized active mass, and the return of the condensate to the alginate solution or homogenized active mass.

[0038] The mixture for the homogenization step may be prepared via at least three alternative processes. It has now been unexpectedly discovered that poorly soluble bioactive materials, especially those with a relatively low melting point, e.g., below 80°C, can be easily combined with an emulsifier, and that poorly soluble bioactive materials can be well and sufficiently dispersed in an aqueous medium containing alginate, even when a small amount of emulsifier is used as described above. One example of such a bioactive material is CoQ10. Furthermore, an emulsifier can be added to the poorly soluble bioactive material or the alginate solution, and yet the poorly soluble bioactive material can be adequately dispersed in the casting solution.

[0039] Thus, in one alternative, the poorly water-soluble bioactive material is combined with an emulsifier and, optionally, with a lipophilic component such as an antioxidant or preservative. Combining such poorly water-soluble bioactive material with an emulsifier may include mixing, melting, or otherwise creating a homogenous mixture of these materials. Alternatively, the alginate is combined with water and other components of an essentially aqueous medium and mixed until dissolved. The time required to substantially dissolve the alginate in the aqueous medium typically depends on the primary dispersant of the powder and its wetting, but dissolution times required to completely dissolve the alginate powder in water range from 15 to 120 minutes, provided that appropriate care is taken to avoid clumping. Dissolution of the alginate may be carried out at any convenient temperature, but it may be advantageous to carry out dissolution of the alginate at an elevated temperature, for example, 50°C to 90°C, preferably 50°C to 60°C. The combination of the poorly water-soluble bioactive material with other ingredients as described above can also be carried out at elevated temperatures, particularly advantageously when the poorly water-soluble bioactive material has a melting point in the same range, such as coenzyme Q10.

[0040] Alternatively, the essentially aqueous medium can be combined sequentially or simultaneously with the alginate and emulsifier as described above and mixed until dissolved. The resulting mixture can be provided with a poorly water soluble bioactive material to provide a mixture ready for the homogenization step.

[0041] Furthermore, the poorly water-soluble bioactive material may be combined with an emulsifier and then thoroughly mixed and combined with, for example, an adsorbent powder. The resulting mixture may then be ground to reduce the particle size of the poorly water-soluble bioactive material. Advantageously, the adsorbent powder may be a powder of any additional components of the film, such as a solid plasticizer (such as xylitol), a filler, an additional film-forming polymer, etc.

[0042] The resulting active mass is then cast onto a substrate after the homogenization step to form a wet film, i.e. the process of the present invention includes a casting step. The wet film thus formed is dried, for example with the aid of a circulating hot air oven. The casting process can be carried out using various methods. In one preferred alternative, said casting is carried out using a slit die assembly. The slit die assembly is an apparatus characterized by a gap-forming plate, by which the active mass is forced onto the substrate under positive pressure or allowed to flow freely onto the substrate, but usually moving at a predetermined speed relative to the static slit die assembly. The slit die assembly is usually in liquid communication with the active mass tank, where the active mass is stored at a controlled temperature until it is cast onto the liner. The slit die apparatus is usually connected to the active mass tank via a pump, usually a peristaltic pump, a piston pump, or a rotor-stator pump, to control the feed rate of the active mass. The slit die apparatus plates can be heated to an optional controlled temperature to maintain or increase the temperature of the active mass. The active mass can also be circulated in the slit die device at a predefined speed, for example to avoid settling of undissolved components and clogging of the slit, and only the required amount can flow out of the die. A further device that can be used for casting is the stretching blade. The stretching blade is a blade that is placed on a substrate with a predefined gap. One or both of the blade or the substrate move relative to the other, and the casting solution is placed forward in front of the stretching blade, allowing the active mass to flow through the gap between the stretching blade and the substrate. The active mass can be fed from an active mass tank, for example via a peristaltic pump, to a position just before the stretching blade. Depending on the width of the stretching blade, multiple feed outlets can be used to ensure uniform casting and to feed the active mass to the stretching blade. Casting can also be carried out by further methods commonly used in fields such as gravure, printing, etc.

[0043] The temperature of the casting step is usually determined by the temperature of the active mass being fed and can be further controlled, for example, by a heated slit die assembly. Although the casting process can be carried out at ambient temperature, it has been found to be particularly advantageous to carry out the process at elevated temperatures, for example, between 40°C and 90°C, preferably between 50°C and 65°C.

[0044] Casting techniques aim to allow for uniform film thickness and uniform distribution of bioactive materials within the film. One of the main properties that generally affects the film casting process and the resulting film is the viscosity of the casting solution before casting on the substrate. While casting in a typical industrial process is performed at ambient temperature, with the active mass having a viscosity range of 4000 cP (mPa*s) to 7000 cP (mPa*s), it has surprisingly been found that by utilizing the masses described herein, continuous slit die casting can be performed at high viscosities, for example, above 12000 cP, and wet film thicknesses of more than 1500 μm and even more than 2000 μm, as shown in the accompanying examples. The wet film thickness of the wet film is usually determined by the gap of the casting device, such as a slit die, a stretching blade, or a knife. In the art, the wet film thickness should not exceed 1000 μm, and is generally preferred to be significantly thinner. However, by providing a casting solution as defined herein, it is possible to cast wet films having thicknesses of more than 1000 μm, for example 1.0-3.0 mm, 1250-3000 μm, or 1250-1800 μm. The viscosity of the active mass used in the casting process is typically between 10 Pa*s and 40 Pa*s at 25° C., or between 5 Pa*s and 35 Pa*s at temperatures between 50° C. and 85° C.

[0045] In a typical industrial process, the film is cast onto a roll of release liner, e.g., a thin (usually less than 100 μm) PET film, stretched at a constant linear speed through a drying chamber, and rerolled at the exit side with the dried formed film on the release liner. Commonly used substrates include plastic sheets such as polyethylene terephthalate (PET), siliconized PET, natural or siliconized biaxially oriented PET (known as Mylar), polytetrafluoroethylene (Teflon), polyethylene, polypropylene, and sometimes stainless steel for tray drying.

[0046] An exemplary industrial continuous coating and drying machine based on a slit ultra-precise coating knife system is the OPTIMAGS MBCD series machine. These machines are able to achieve more precise coating and higher film uniformity than those commonly applied in aqueous solvent evaporation film formation processes. It is worth noting that according to the OPTIMAGS guidelines for oral films, the maximum viscosity of the active mass is 7000 cP, casting is preferably carried out at ambient temperature, and the maximum wet film thickness of the coated active mass is up to 1000 μm. It should be noted that in order to achieve the intended high dosage, low drying thickness variation, and high content uniformity of the inventive film, industrial production of the inventive film by slit die casting at generally unacceptably high viscosities and high wet film thicknesses may be required, which are much higher than those achieved industrially.

[0047] Additionally, the process may further include cutting the formed film into desired shapes, e.g., strips, and filling suitable single or multi-unit packaging, such as sachets or cassettes. Single unit sachet packaging is preferably a heat sealed aluminum foil laminate.

[0048] In certain specific embodiments, the process according to the invention comprises steps i) providing a casting solution having a composition generally as described above, ii) casting the casting solution onto a substrate to provide a wet film, and iii) drying the wet film to a desired residual moisture to obtain a dry film (i.e., a dried film), the casting solution comprising a solution of an alginate and an emulsifier in an aqueous medium, and further comprising a bioactive material that is essentially insoluble in the casting solution.

[0049] In a further particular embodiment, the process according to the invention comprises the following steps: i) providing a poorly soluble bioactive material, ii) providing an aqueous alginate solution comprising an emulsifier, iii) mixing the poorly soluble bioactive material of step i) with the alginate solution of step ii), iv) homogenizing the resulting mixture to provide a casting solution, v) casting the casting solution obtained in step iv) on the surface of a substrate to obtain a wet film, and vi) drying the wet film to obtain a dry film, which is a stable, homogenous, solid, mucoadhesive film comprising the poorly soluble bioactive material for oral administration.

[0050] In an alternative specific embodiment, the process according to the invention comprises step i) of mixing said poorly soluble bioactive material with an emulsifier in a non-aqueous environment, step ii) of providing an aqueous alginate solution, step iii) of mixing the mixture prepared in step i) with the alginate solution of step ii), step iv) of homogenizing the resulting mixture to provide a casting solution, step v) of casting the casting solution obtained in step iv) on the surface of a substrate to obtain a wet film, and step vi) of drying the wet film to obtain a dry film, which is a stable, homogenous, solid film comprising said poorly soluble bioactive material for oral administration.

[0051] Similarly, the alginate solution may further include the ingredients buffers, chelating agents, plasticizers, antioxidants, minerals, bulking agents, co-film-forming polymers, stabilizers, flavors, and colorants, generally as set forth below. These materials may be added to either the aqueous alginate solution, the poorly soluble bioactive material, or a mixture thereof, during the film preparation process.

[0052] Poorly soluble bioactive materials can be added to the alginate solution of the process.The homogenization process can then be carried out using methods known in the art, such as a high-pressure piston homogenizer or a shear type, such as a high-speed Ultra-Turrax disperser.Preferably, the homogenization process is carried out by vigorous stirring at high shear rates, optionally using an Ultra-Turrax type disperser, to emulsify the mixture.

[0053] In some embodiments, the poorly soluble bioactive material may be milled prior to addition to the alginate solution, for example with additional solid components of the film. Without being bound by theory or mechanism of action, it is believed that milling the poorly soluble bioactive material at this stage may provide a more homogenous dispersion of the active material within the active mass and film. Such a separation step may allow for better control of particle size and prevent melt sticking and loss to container surfaces.

[0054] In a further aspect, provided herein is an orally administrable mucoadhesive film prepared according to the methods described herein.

[0055] In accordance with the principles of the present invention, at least one bioactive material utilized in the film of the present invention is a bioactive material that is poorly water soluble. The terms "poorly soluble bioactive material" or "poorly water soluble bioactive material" and terms such as "drug", "active agent", "active pharmaceutical ingredient", "biologically active", and the like, used interchangeably herein, in conjunction with the terms "poorly soluble" or "poorly water soluble", refer to a bioactive material that has a solubility of less than 0.01 g / L (i.e., 10 ppm), more preferably less than 0.001 g / L (i.e., 1 ppm).

[0056] A poorly soluble bioactive material may also be present in the film in an undissolved state, i.e., the bioactive material is essentially insoluble in the film. Thus, a bioactive material that is essentially insoluble in the film is not only poorly soluble in aqueous solutions, but also insoluble in the wet film or active mass. As described in more detail below, the water content in the wet film may be determined based on the desired final viscosity, for example, between 7 and 40 Pa*s, or between 10 and 40 Pa*s, as described herein, and as measured according to the method of the Examples. Thus, a bioactive material that is substantially insoluble in the film will be present primarily in undissolved form in a wet film that includes an alginate film former and all other excipients in a sufficient amount of water and / or co-solvents to produce a viscosity of 7-40 Pa*s at 20°C. Thus, even if the film composition or wet film includes various co-solvents, surfactants, and / or oils, the bioactive material will not dissolve to a significant extent in the solvent therein, as described above.

[0057] The term "biologically active", which is used interchangeably herein with terms such as "drug", "active agent", "active pharmaceutical ingredient", "biologically active", refers to a substance of natural or synthetic or semi-synthetic origin that is used to alleviate or treat or prevent a disease or health disorder such as migraine, multiple sclerosis, Parkinson's or Alzheimer's disease, depression, dementia, anxiety, insomnia, fatigue, or that is known to have a positive or negative effect on at least some human biological systems, such as decreasing or increasing the level of an essential nutrient, inter alia, with the aim of preventing or reversing a deficiency. The term also refers to a natural product or an essential nutrient, inter alia, a material of natural or synthetic or semi-synthetic origin that has the same chemical structure as the natural product or modified natural product. This term may refer to materials that may be minerals, one or more vitamins and provitamins or vitamin analogs or vitamin-like substances, omega-3 fatty acids, antioxidants, CoQ10, cannabinoids, terpenes, flavonoids, antifungals, plant extracts, steroids, phytosterols, polyphenols, poorly soluble phenols, carotenoids such as lutein, and phosphatidylserine. A particularly preferred example of a poorly water-soluble bioactive substance is CoQ10. As described in more detail below, CoQ10 presents a challenge to incorporate water-insoluble bioactive substances at high loadings into oral alginate films. Further preferred examples of poorly soluble bioactive materials include omega-3 fatty acids, vitamin E, turmeric water-insoluble extracts, lecithin, and lutein.

[0058] It has now surprisingly been found that by utilizing the process described herein, a relatively low concentration of emulsifier is sufficient or necessary to provide the beneficial effect of contributing to the stabilization of poorly soluble drugs, such as CoQ10, in a hydrophilic alginate matrix. The content of emulsifier may be less than 1 / 5 of the drug content, preferably less than 1 / 10, less than 1 / 20, or less than 1 / 50 of the drug content, and less than 1 / 100 of the drug content. Thus, the content of emulsifier is preferably between 1 / 20 and 1 / 100 of the drug content, and is currently particularly preferred to be between 1 / 50 and 1 / 60 of the content of poorly water-soluble bioactive material. Thus, a higher loading of drug can be achieved with a weight percent ratio between drug and alginate in the film of the present invention higher than 1:2.5, for example higher than 1:2, higher than 1:1. In some embodiments, the weight ratio of agent to alginate is between about 1:2.5 and about 2.5:1, such as between 1:2 and 2.5:1, such as between 1:1 and 2.5:1. Preferably, the weight ratio of bioactive material to alginate is between about 1:2 and about 2.5:1.

[0059] Thus, the loading of bioactive material, i.e., the total amount of bioactive material in the dry film expressed as % by weight of the film, is greater than about 5% by weight, preferably greater than 10% by weight, for example between 10% and 50% by weight, or between 15% and 45% by weight. Thus, orally administrable mucoadhesive films in which the concentration of poorly water-soluble bioactive material in the film is greater than 10% by weight of the dry weight of the film form a further aspect of the invention.

[0060] The poorly water-soluble bioactive material in the film according to the invention contains 5-30 mg, e.g. 7 to 15 mg, of drug per square centimetre of dry film, the thickness of the dry film varying from 50 to 600 μm, preferably 100 to 400 μm. Preferably, the orally administrable mucoadhesive film contains 5-20 mg of poorly water-soluble bioactive material per square centimetre of dry weight of the film, thus forming a further aspect of the invention.

[0061] The thickness of the film is usually determined by the thickness of the wet film cast on the substrate and the drying conditions, but of course also by the formulation. For example, if a high drug dosage is required, the film may be prepared with a thicker thickness and / or applied in larger pieces, but this may impair oral residence time and / or palate adhesion, not to mention patient compatibility. The thickness of the film after drying of the present invention, i.e., the thickness of the film obtained after drying the wet film to the target moisture content value, is usually about 0.030 to about 3.0 mm, more preferably about 0.10 to about 1.0 mm.

[0062] Moreover, according to the principles of the present invention, the content of emulsifier required to achieve advantageous stabilization of said bioactive material in the alginate matrix is ​​lower than the content of bioactive material in the film. The content of emulsifier is usually less than 1 / 5 of the content of bioactive material, preferably less than 1 / 10 of the content, less than 1 / 25 of the content, even less than 1 / 50 of the content of bioactive material, and not more than 1 / 100 of the content of drug. Thus, the content of emulsifier is preferably between 1 / 20 and 1 / 100 of the content of drug, and currently is particularly preferably between 1 / 50 and 1 / 60 of the content of poorly water-soluble bioactive material.

[0063] Emulsifiers that can be used at relatively low concentrations in accordance with the present invention include any suitable emulsifier that is compatible with poorly soluble bioactive materials, such as cationic emulsifiers, anionic emulsifiers, zwitterionic emulsifiers, nonionic emulsifiers, and the like.

[0064] Preferably, the emulsifier utilized as above is a selected phospholipid, such as phosphatidylethanolamine, phosphatidylinositol, phosphatidylserine, lecithin and their derivatives. In a currently preferred embodiment, the emulsifier is lecithin. The lecithin can be solid lecithin or, preferably, liquid lecithin.

[0065] The emulsifier may also be selected from the group consisting of phospholipids, bile salts, sorbitan fatty acid esters, ethoxylated sorbitan esters, sucrose fatty acid esters, ethoxylated fatty acid esters or fatty alcohol ethers, and combinations thereof. Suitable emulsifiers also include PEG-fatty acid glycerides, such as polyethylene glycol 12-hydroxystearic acid. Sorbitan fatty acid esters are also known by the name Span, such as sorbitan monolaurate (Span 20), sorbitan monopalmitate (Span 40), sorbitan monostearate (Span 60), sorbitan tristearate (Span 65), sorbitan monooleate (Span 80), sorbitan trioleate (Span 85), and sorbitan sesquioleate (Span 83). Also, as ethoxylated sorbitan esters, there are known names such as Tween, e.g., polyoxyethylene (20) sorbitan monolaurate (Tween 20), polyoxyethylene (20) sorbitan monopalmitate (Tween 40), polyoxyethylene (20) sorbitan monostearate (Tween 60), polyoxyethylene (20) sorbitan monooleate (Tween 80). As sucrose fatty acid esters, there are known names such as Sisterna or Ryoto materials, e.g., sucrose stearate (Sisterna SP50, Sisterna SP70), sucrose palmitate (Sisterna PS750), ethoxylated fatty acid esters, and ethoxylated fatty alcohol ethers. It is to be noted that the use of lecithin is highly advantageous because it is a non-allergenic material derived from natural plants and can be a single safe emulsifier in the film transport system of the present invention.

[0066] The alginate utilized in the present invention as the primary film-forming agent can be one or a mixture of several types. The alginate can be derived from brown algae, microbial fermentation, or synthetic sources, and can also be synthetically modified, such as propylene glycol alginate. In a currently preferred embodiment, the alginate of the present invention is sodium alginate. The alginate utilized in the present invention can be one single grade or a combination of several different grades. It should be understood that alginate grades are usually classified by their apparent viscosity, and the alginate grade or blend of grades utilized can be of any suitable nominal viscosity. The preferred alginate of the present invention is a blend of several grades, most preferably a blend of a low viscosity grade and a very low viscosity grade.

[0067] [Table 1]

[0068] Table 1 above shows a partial list of alginate products that represent viscosity grades. Apparent viscosity is generally assayed at a specified weight percent of alginate in aqueous solution and measured on a Brookfield RV viscometer using spindle #2 at 20 rpm and 20°C.

[0069] The poorly soluble bioactive material can be CoQ10. The CoQ10 used in the film of the present invention is CoQ10, and its derivatives and analog compounds have the following structural formula:

[0070] [ka] Here, R 1 is selected from the group: 1) A chain of 6 to 10 isoprenyl groups: [ka] or 2) C5~C 15A straight or branched alkyl having a carbon chain, which may be substituted with an alkyl group having a C1-C6 carbon chain, a hydroxyl group, or modified with a cationic moiety, especially a triphenylphosphonium group.

[0071] Other poorly soluble bioactive materials may include cannabinoids. The cannabinoids of the present invention may be pure or crude or semi-purified plant extracts, or synthetic or semi-synthetic cannabinoids, or cannabinoid analogs such as CBD, THC, or endocannabinoids such as anandamide, or a blend of two or more cannabinoids. The poorly soluble vitamins used in the films of the present invention may be selected from the group consisting of vitamin A, vitamin D, vitamin E, and vitamin K. The plant extracts may be selected from the group consisting of delphinoll, pycnogenol, saffron, lutein, and allagan oil. Antifungal agents include, for example, clotrimazole, econazole, lanoconazole, and the like. Terpenes include both terpenes and terpenoids, such as geraniol, citral, menthol, myrcene, limonene, and the like. Specific examples of phytosterols include cyclic alcohols such as β-sitosterol, stigmasterol, brassicasterol, and campesterol. Specific examples of flavonoids include tiliroside, quercetin, kaempferol, rutin, luteolin, isoflavone, etc. Specific examples of sparingly soluble phenols include caffeic acid, sesamol, curcumin, ellagic acid, etc.

[0072] The films may further comprise additional excipients such as plasticizers, sweeteners, bulking agents, co-film formers, stabilizers including antioxidants, preservatives, buffers, chelating agents, flavors, colors, and the like.

[0073] Plasticizers are materials known in the art that impart flexibility to films. Plasticizers suitable for the purposes of the present invention are generally compatible with alginate. Suitable plasticizers include polyols such as sucrose, mannitol, sorbitol, xylitol, polyethylene glycols (PEGs) such as PEG400, and glycerin. A particularly preferred plasticizer is xylitol.

[0074] Plasticizers, especially sugars, can also impart a pleasant taste to the film, however, additional natural or synthetic high intensity sweeteners may be used, including sucralose, stevia, aspartame, acesulfame potassium, and naringin dihydrochalcone.

[0075] The film may further comprise a filler, i.e., a bulking agent, as known in the art. The purpose of the bulking agent in the film may be to aid in the disintegration of the film or to increase the solids content of the active mass. These include microcrystalline cellulose and insoluble fiber.

[0076] The film may further comprise additional film formers (co-film formers), for example, to aid in the formation of the alginate film or to improve its mechanical or sensory properties. Suitable additional film formers include maltodextrin, pullulan, and soluble cellulose derivatives such as hypromellose (hydroxypropyl methylcellulose: HPMC), hydroxypropyl cellulose, hydroxyethyl cellulose, etc. Other co-film formers include proteins such as gelatin, and starch or modified starch. The amount of any of these film formers is less than the amount of alginate in the film. Preferably, the cumulative amount of all co-film formers is less than the amount of alginate in the film.

[0077] The film may further include a stabilizer, for example, to prevent degradation of the film's components or to prevent their interaction. Suitable preferred stabilizers include xanthan gum and carrageenan, and may also include gum arabic. Antioxidants typically can prevent oxidation by atmospheric oxygen or metal impurities. Suitable preferred antioxidants include ascorbyl palmitate and tocopherol, and may also include traditional pharmaceutical antioxidants such as ascorbic acid, thiols, or bisulfites. Preservatives typically may prevent or inhibit microbial growth within the film. Suitable preservatives include sorbates or benzoates. Buffers typically assist in maintaining the pH value of the film. Suitable preferred buffers include citric acid, citrates such as sodium citrate, and may also include phosphates or acetates. Chelating agents may be used to reduce the free concentration of certain metals, including calcium. Calcium may be involved in chemical interactions with the film's components and may be a necessary microbial element. Preferred chelating agents include ethylenediaminetetraacetic acid (EDTA) and its salts, such as the sodium salt, and may also include amino acids. Suitable emulsifiers are generally described above, however, the films may include combinations of emulsifiers, and combinations of emulsifiers and co-emulsifiers, as are known in the art.

[0078] These films may further include flavorings and colorants to improve the palatability and appeal of the product. Suitable preferred flavorings include plant extracts including oils and oleoresins, and may include mint extracts, and citrus oils in particular. In general, the term "flavoring agent" as used herein refers to a group of chemical agents or molecules that may alter the flavor of other substances. Flavoring agents may be naturally derived or synthetic, and include esters such as isoamyl acetate, ethyl propionate, terpenes such as menthol, limonene, alkamides such as spilanthol, amino acids, peptides such as glutamic acid, synthetic or natural compounds combined to mimic, enhance or mask natural flavors, and mixtures of natural and synthetic compounds. Suitable preferred colorants include chlorophyll, E110 (disodium 6-hydroxy-5-[(4-sulfophenyl)azo]-2-naphthalenesulfonate, also known as Sunset Yellow), and E132 (5,5'-indigodisulfonic acid sodium salt, also known as Indigo Carmine and Blue FD&C #2).

[0079] The films may further include minerals such as titanium dioxide to provide opacity or color.

[0080] In some further embodiments, the films of the present invention may further comprise a water-soluble bioactive material selected from the group consisting of vitamins, antioxidants, minerals, triptans, micronutrients, and homeopathic remedies. The concentration of the additional bioactive material in the final film may range from 0.001% to 20% by weight.

[0081] The films of the present invention may be characterized by an oral residence time of between about 1 minute and about 90 minutes, more preferably between about 5 minutes and 30 minutes. In addition, the films may typically have acceptable color and flavor, and good mouthfeel. Mouthfeel may be judged by either professional or amateur sensory panel evaluation. In addition, the films of the present invention typically have good adhesion to the palate, are flexible when handled, non-sticky, and non-oily. The films of the present invention may be applied to a variety of oral locations. The orally administrable mucoadhesive films may be anywhere in the oral cavity, most preferably on the palate, or under the tongue.

[0082] The films of the present invention typically exhibit an acceptable shelf life, i.e., the film undergoes minimal mechanical, physical or chemical changes, preferably for at least two years, when stored under appropriate conditions, e.g., at controlled room temperature (25°C, in the range of 15°C to 30°C). Recommended storage is in an unopened sealed package in a dark place at ambient temperature. Under such storage, the product is suitable for use, i.e., there is no substantial chemical or physical deterioration or microbial spoilage that would prevent safe and effective use of the product. As shown in the accompanying examples, the film maintains its physical appearance and mechanical stability during storage over time.

[0083] Unit Dose The area, length and width of the film strip of the present invention are determined by the required dosage and drug loading in the film. The area of ​​the unit dosage can vary between 1 square centimeter and 25 square centimeters, for example, between about 1 x 1 cm and about 5 x 5 cm. Preferably, the area of ​​the unit dosage of the film is between about 6 and about 12 square centimeters. The preferred length to width ratio is between 1:1 and 3:1, for example, between 1.5:1 and 2.5:2. According to some embodiments, the dosage of the bioactive material in a single film strip can range from about 10 mg to about 200 mg. In some currently preferred embodiments, the dosage of the bioactive material is between about 40 mg and about 160 mg, more preferably between about 60 mg and about 100 mg.

[0084] The term "chemically stable film" may be used interchangeably with the term "stable film" herein or in the claims, and refers to a film that, when stored under suitable storage conditions at ambient temperature, e.g., packaged in a sealed aluminum foil laminate, retains its chemical and physical integrity, i.e., does not leach, change its composition or appearance, or disintegrate, and has a shelf life of at least 2 years. The chemical stability of the film of the present invention is defined such that no more than 10% of the original active ingredient concentration in the film is degraded upon suitable storage as described above.

[0085] The term "about" as it appears in this specification and claims refers to a target set point of ±10% of the value with which the term is associated. EXAMPLES

[0086] bending resistance The measurement of fold resistance as used herein can often exemplify and represent the mechanical strength and elasticity of a film. Fold resistance was measured by folding the film multiple times at the same point until it broke. Using 8x2cm strips of film, each sample was folded upwards to 90° and then folded downwards again to 90° on the other side. The scores are as follows: 1, breaks after one fold; 2, cracks after two folds; 3, cracks after three folds; 4, cracks after five folds; and 5, no cracks after 10 repetitions.

[0087] Oral residence time Oral residence time in volunteers was assessed by cutting the film into strips, placing and adhering the strips to the roof of the mouth of the volunteers, and measuring the time until the physical presence of the swollen film formed was no longer detectable.

[0088] Dry Film Thickness The measurements were performed using a MOTOKO handheld electronic micrometer model, MT211101, with a reading accuracy of ±1 μm.

[0089] viscosity Unless otherwise specified, measurements were performed using a Brookfield-AMETEK DV2T viscometer. Detailed measurement conditions are described below.

[0090] Moisture content The films were cut into strips measuring 8x2cm and incubated at 25°C and the relative humidity was recorded. Samples were weighed before incubation and every 24 hours until a stable weight was reached. Samples were dried over copper(II) sulfate in a desiccator at 110°C for 4 hours, stored for 24 hours and reweighed to determine moisture content.

[0091] pH measurement Measurements were performed using a HANNA digital pH meter model HI2211.

[0092] Device High shear homogenization was performed using the following equipment: DLS (VELP Scientifica) with overhead lab stirring type with shear impeller: bladed disk with 45 mm diameter and 10 vertical blades with width of 5 mm and height of 10 mm at 20 degrees to the shaft, or Ultra-Turrax by DAIHAN homogenizer HG-15A with Φ20 mm dispersion tool rotor and Φ25 mm stator, maximum allowed speed of 15000 rpm. All other equipment used is described in the examples below.

[0093] All materials used in the examples were sourced from the sources stated in the specification. The lecithin used in all examples was liquid sunflower lecithin (E-322) Giralec (Lasenor Emul SL, Spain).

[0094] [Example 1] Preparation of CoQ10 films The detailed amounts of each material used are summarized in Table 2 below.

[0095] [Table 2]

[0096] CoQ10 powder (ubiquinone (Kaneka)) was melted with lecithin and tocopherol at 60°C in a glass beaker placed in a water bath.

[0097] In a separate container, sodium alginate (Satialgine S20NS and Satialgine S60NS from Algaia) was dissolved in deionized water at 50°C. Stevia and xylitol were then added to the solution and dissolved at 50°C. The molten CoQ10 mixture was added to the alginate solution held at 55°C and mixed with a high shear impeller at 1500 rpm for 20 minutes to obtain a homogenous mixture. Flavoring agents were then added and mixed uniformly under continuous heating to maintain 55°C.

[0098] The obtained active mass was cast onto a 125 μm thick PET liner (manufactured by DuPont) using a drawing blade with a nominal gap of 1500 μm, and dried in a forced air drying oven at 80° C. for 40 minutes.

[0099] result The resulting dry film thickness was 0.282 ± 0.015 mm and the weight per area was 387 gr / m 2 The coenzyme Q10 content was 13.1 mg / cm 2 The oral acceptability was tested by placing the film on the tongue and adhering it to the roof of the mouth. The film was found to have good taste, good mouth feel, and good adhesion to the roof of the mouth. The oral disintegration time was greater than or equal to 3 minutes. When the film was handled, it was non-sticky, non-oily, and flexible.

[0100] [Example 1a] Comparative homogenization process The ingredients used are shown in Table 3 below.

[0101] A premix of CoQ10 powder (ubiquinone (Kaneka)), lecithin and tocopherol was melted at 60°C (in a glass beaker placed in a water bath) and slowly added to deionized water preheated to 55°C, thoroughly dispersed with an Ultra-Turrax, and shear mixed at 20%, 30%, 40% and 50% of the machine's maximum speed for 1 minute intervals while maintaining the temperature between 54.5°C and 57.3°C.

[0102] Sodium alginate (Satialgine S20NS and Satialgine S60NS from Algaia), stevia and xylitol were mixed uniformly and slowly added to the CoQ10 emulsion and completely dissolved in a flow turbo impeller at 1500 rpm for 25 minutes at 59° C. Flavoring agents were added, followed by stirring at 400 rpm for 15 minutes at 57° C. to remove air bubbles.

[0103] [Table 3]

[0104] The viscosity of the active mass formed was 5400 cPs (spindle #4, 20 RPM, 57° C.).

[0105] The resulting active mass was cast onto a 57° C. PET liner using a drawing blade with a nominal gap of 1500 μm and dried in a forced air drying oven at 80° C. for 45 minutes.

[0106] The same CoQ10:alginate ratio, percent CoQ10 in the dry film, active mass casting, and drying were used in this example and in Example 1. Unlike the film formed by the method of Example 1, the film formed was dry and uneven with some cracks and gaps.

[0107] The thickness of the film was 0.167±0.010 mm, the weight per area was 258 GSM, and the content of coenzyme Q10 was 5.8 mg / cm. 2 The film was a uniform orange color with good flavor and mouthfeel. The oral disintegration time was about 2 minutes and the folding resistance score was 5.

[0108] [Example 2] Film preparation, continuous drying process CoQ10 powder (Ubiquinone, Kaneka) was melted with lecithin and tocopherol at 60°C in a glass beaker placed in a water bath. In a separate container, citric acid and trisodium citrate were added to deionized water until the pH was 5.5. Sodium alginate (Satialgine S20 and Satialgine S60, Algaia) was dissolved in the above aqueous solution at 50°C. Stevia, xylitol, and maltodextrin were then added to the aqueous alginate solution and dissolved at 50°C. The molten CoQ10 mixture was added to the alginate solution at 55°C and mixed with a high shear impeller at 1500 rpm. Flavoring agents were then added. The amounts are shown in Table 4 below.

[0109] [Table 4]

[0110] The obtained active mass is characterized by a viscosity of 20000 cP at 50°C (VEVOR digital rotational viscometer model NDG 8S, spindle #4, 12 rpm). Casting and drying of the active mass was carried out on a PTE release liner at 50°C using a U-shaped Optimags MBCD 1.3-3.1 machine. The machine has a drying length of 1600 mm and two drying zones. The web linear speed was 0.05 m / min, which corresponds to a drying time of about 32 minutes. The temperature of the first zone was 70°C and that of the second zone was 100°C.

[0111] result The thickness of the wet film during drying in continuous operation was 1275 μm, and wet films with a thickness greater than 1275 μm were dried in a drying oven.

[0112] The resulting dry film had a moisture content of approximately 12% and a thickness of 307±0.015mm with a weight per area of ​​409gr / m 2and was tested for oral acceptability (taste, adhesion and residence time). The film was found to be flexible, uniform, with good flavor, good mouth feel and good adhesion to the roof of the mouth. Oral disintegration time was 3-5 minutes.

[0113] When handled, the film was non-sticky and non-greasy and scored a 5 in the fold resistance test.

[0114] The uniformity of the resulting film was calculated by weighing seven samples of 1.9 cm x 1.9 cm. The samples were taken from different parts of the produced film roll, two samples from each side, and three samples were taken from the centre of the resulting 1 meter long roll.

[0115] The weight per area of ​​the film sample is calculated by the area (3.8 cm 2 ) and calculated as grams per square meter (GSM).

[0116] The average weight was found to be 409 GSM with a low standard deviation (SD) of 4%. The SD achieved for the film obtained utilizing the process of the present invention is significantly lower than that found in other conventional film processes (SD of about 10%).

[0117] The results are shown in Table 5.

[0118] [Table 5]

[0119] The moisture content was determined to be 11-15 wt% by loss on drying.

[0120] Cut the film into 2.5cm x 3.2cm (area 8cm 2 The average weight of the units was approximately 327 mg, and the calculated average content was approximately 100 mg of CoQ10 per unit.

[0121] [Example 3] Milled formulation The detailed amounts of each material used are summarized in Table 6 below.

[0122] [Table 6]

[0123] CoQ10 (ubiquinone (Kaneka)) powder was melted with lecithin and tocopherol at 60° C. The molten mixture was then poured into an electric high-speed rotary knife grinder containing xylitol at short intervals for approximately 3 minutes, maintaining the temperature below 40° C. The resulting particles were passed through a 60 mesh sieve.

[0124] In a separate container, sodium alginate (Satialgine S20NS and Satialgine S60NS (Algaia)) was dissolved in deionized water at 50° C. Stevia was then added to the solution and dissolved at 50° C.

[0125] The finely ground mixture powder was then added to the alginate solution at 55°C and mixed with a high shear impeller at 1500 rpm for 20 minutes, after which the flavourings were added and mixed.

[0126] The resulting active mass was cast onto a liner using a drawing blade with a nominal gap of 1500 μm and dried in a forced air drying oven at 80° C. for 40 minutes.

[0127] result The resulting dry film thickness was 0.228±0.030mm and the weight per area was 312gr / m 2 The coenzyme Q10 content was 7.0 mg / cm 2The film was tested for oral acceptability (taste, adhesion and residence time). The film was found to have good flavor, good mouth feel and good adhesion to the roof of the mouth. The oral disintegration time was about 3-5 minutes. The film was non-sticky and non-greasy when handled.

[0128] [Example 4] Melting CoQ10 in the absence of additional ingredients This formulation was carried out by incorporating the lecithin component into the aqueous film-forming polymer solution, while the CoQ10 was melted at 60° C. without any additional ingredients. The molten CoQ10 was added to the aqueous solution as described in the previous examples.

[0129] The formed active mass was then cast using a drawing blade with a gap of 1000 μm and dried at 90°C.

[0130] [Table 7]

[0131] result The thickness of the formed film was 0.300±0.015 mm and the folding resistance score was 4. The surface of the film was non-oily and non-sticky.

[0132] [Example 5] High dose of CoQ10 The detailed amounts of each material used are summarized in Table 8 below.

[0133] CoQ10 (ubiquinone (Kaneka)) powder was melted at 60°C together with lecithin and tocopherol.

[0134] In a separate container, sodium alginate (Satialgine S20NS and Satialgine S60NS from Algaia) was dissolved in deionized water at 50°C. Stevia and xylitol were then added to the solution and dissolved at 50°C. The molten CoQ10 mixture was added to the alginate solution held at 55°C and mixed with a high shear impeller at 1500 rpm for 20 minutes to obtain a homogenous mixture. Flavoring agents were then added and mixed uniformly under continuous heating to maintain 55°C.

[0135] [Table 8]

[0136] The resulting active mass was cast onto a liner using a drawing blade with a nominal gap of 1000 μm and dried in a forced air drying oven at 110° C. for 12 minutes.

[0137] result The resulting dry film thickness was 0.402±0.038mm and the weight per area was 250gr / m 2 The coenzyme Q10 content was 10.9 mg / cm 2 The film was tested for oral acceptability (taste, adhesion and residence time). The film was found to have good flavor, good mouth feel and good adhesion to the roof of the mouth. The fold resistance was scored as 5. The film was non-sticky and non-greasy when handled.

[0138] [Example 6] Omega-3 Oil The formulation composition and amounts of the ingredients are shown in Table 9 below.

[0139] Sodium alginate (Satialgine S20NS and Satialgine S60NS from Algaia) was dissolved in deionized water along with xylitol and maltodextrin at 50° C. The alginate solution was added to lecithin at 50° C. to obtain a homogenous solution. Omega-3 oil (BASF) was added to the solution at 50° C. and mixed with a high shear impeller at 1500 rpm for 20 minutes to obtain a homogenous solution.

[0140] The resulting active mass was cast onto a liner using a drawing blade with a nominal gap of 1000 μm and dried in a forced air drying oven at 110° C. for 12 minutes.

[0141] [Table 9]

[0142] The resulting dry film had a thickness of 0.246±0.014 mm and a weight per area of ​​410 GSM. The Omega-3 content was 11.1 mg / cm 2 The fold resistance was scored as 5. Oral acceptability (adhesion and residence time) was typical to good with good mouth feel and good adhesion to the palate. The film was light in color and smooth in texture. When handled, the film was non-sticky with slight oil fluting that diminished over time.

[0143] [Example 7] Natural Vitamin E The formulation composition and amounts of the ingredients are shown in Table 10 below.

[0144] Sodium alginate (Satialgine S20NS and Satialgine S60NS from Algaia) was dissolved in deionized water along with xylitol and maltodextrin at 50° C. The alginate solution was added to lecithin at 50° C. to obtain a homogenous solution. Natural Vitamin E (DSM) was added to the solution at 50° C. and mixed with a high shear impeller at 1500 rpm for 20 minutes to obtain a homogenous solution.

[0145] The resulting active mass was cast onto a liner using a drawing blade with a nominal gap of 1000 μm and dried in a forced air drying oven at 110° C. for 12 minutes.

[0146] [Table 10]

[0147] The resulting dry film had a thickness of 0.234±0.010 mm and a weight per area of ​​343 GSM. The natural vitamin E content was 9.3 mg / cm. 2 The fold resistance was scored as 5. Oral acceptability (adhesion and residence time) was typical and good with good mouth feel and good adhesion to the roof of the mouth. The film is light in color and has a smooth texture. When the film is handled, it is non-sticky.

[0148] [Example 8] Turmeric addition ratio 1:1 The formulation composition and amounts of the ingredients are shown in Table 11 below.

[0149] Sodium alginate (Satialgine S20NS and Satialgine S60NS from Algaia) was dissolved in deionized water along with xylitol and maltodextrin at 50° C. Turmeric powder (Bara, Israel, Lot: CLP1911419) was added to the solution along with lecithin and mixed with a high shear impeller at 1500 rpm for 20 minutes at 50° C. to obtain a homogenous solution.

[0150] The resulting active mass was cast onto a liner using a drawing blade with a nominal gap of 1000 μm and dried in a forced air drying oven at 110° C. and 60° C. for 14 and 20 minutes, respectively.

[0151] [Table 11]

[0152] The film properties were similar at all drying temperatures.

[0153] The resulting dry film had a thickness of 0.296±0.017 mm and a weight per area of ​​410 GSM. The turmeric content was 11.4 mg / cm. 2 The fold resistance was scored as 5. Oral acceptability (taste, adhesion and residence time) was typical and good, with a pleasant taste, good mouthfeel and good adhesion to the palate. The film is non-sticky.

[0154] The film was orange in color and few particles of turmeric were not well dispersed in the solution.

[0155] [Example 9] Lecithin addition ratio 2.5:1 The formulation composition and amounts of the ingredients are shown in Table 12 below.

[0156] Sodium alginate (Satialgine S20NS and Satialgine S60NS from Algaia) was dissolved in deionized water along with xylitol and maltodextrin at 50° C. The alginate solution was added to the lecithin and mixed with a high shear impeller at 1500 rpm for 20 minutes at 50° C.

[0157] [Table 12]

[0158] The resulting active mass was cast onto a PET liner using a drawing blade with a nominal gap of 1000 μm and dried in a forced air drying oven at 110° C. for 22 minutes.

[0159] The resulting dry film had a thickness of 0.573±0.381 mm and a weight per area of ​​739 GSM. The lecithin content was 11.1 mg / cm 2The fold resistance was scored as 5. The film was light brown in color and contained some agglomerates of poorly dispersed powder. The film was non-tacky but exhibited a slight oiliness.

[0160] [Example 10] Lecithin as a bioactive material added at a ratio of 1:1 The formulation composition and amounts of the ingredients are shown in Table 13 below.

[0161] Sodium alginate (Satialgine S20NS and Satialgine S60NS from Algaia) was dissolved in deionized water along with xylitol and maltodextrin at 50° C. The alginate solution was added to the lecithin and mixed with a high shear impeller at 1500 rpm for 20 minutes at 50° C.

[0162] The resulting active mass was cast onto a PET liner using a drawing blade with a nominal gap of 1000 μm and dried in a forced air drying oven at 110° C. for 18 minutes.

[0163] [Table 13]

[0164] The resulting dry film had a thickness of 0.216±0.011 mm and a weight per area of ​​504 GSM. The lecithin content was 13.1 mg / cm 2 The fold resistance was scored as 5. The film was yellow in color and had small agglomerates of poorly dispersed powder, much smaller than Example 8. The film was non-tacky but exhibited a slight oiliness.

[0165] [Example 11] Lutein supplementation ratio 1:2 First, an alginate solution was prepared: xylitol, maltodextrin, and alginate (Protanal LFR 5 / 60) (FMC / Dupont) were dissolved in deionized water at ambient temperature (approximately 22° C.) by mixing with a high shear impeller at 1500 rpm for 20 minutes.

[0166] The viscosity of the alginate solution was 2700 cPs (spindle #4, 20 rpm, 22° C.).

[0167] Lutein (20% LycoRed, Lyc-O-lutein in safflower oil and a small amount of rosemary extract) and lecithin were then added to the alginate solution at room temperature and mixed with a high shear impeller at 1500 rpm for 20 min to form a combined active mass.

[0168] [Table 14]

[0169] The viscosity of the active mass was 4200 cPs (spindle #4, 20 rpm, 22° C.).

[0170] The active mass was cast onto a PET liner using a drawing blade with a nominal gap of 500 μm and dried in a forced air oven at 90° C. for 10 minutes.

[0171] The resulting dry film had a thickness of 0.214±0.010 mm. The resulting film had an area weight of 390 GSM. The lecithin content was 14.3 mg / cm. 2 The resulting film had a residence time of approximately 90 seconds and showed moderate adhesion to the palate. The film was easily cut into dosage units, was flexible, and received a folding resistance score of 2. Flavor and mouthfeel were mellow and acceptable.

[0172] [Comparative Example 1] The purpose of this trial is to carry out a comparative example based on JP 2018-203618 A.

[0173] The compositions of the solutions prepared are shown in Table 15 below.

[0174] Preparation 1 was a solution containing 20% ​​octenyl succinic anhydride (OSA) starch. Preparation 2 was a solution containing 20% ​​OSA starch and xylitol (1:1 ratio). Preparation 3 had the composition of Example 5 in JP 2018-203618. Preparation 4 had the composition of Example 6 in JP 2018-203618.

[0175] [Table 15]

[0176] OSA starch was weighed according to the table above and added to purified water with mixing. The pH was adjusted to 5-8 with trisodium citrate / citric acid. The mixture was heated to 60°C and mixed until dissolved. CoQ10 was then added to the 60°C solution and homogenized with an Ultra-Turrax applying shear mixing at 1-minute intervals for a total of 2 minutes at 40% of the maximum equipment speed. Alginate LFR was then added and mixed thoroughly at 60°C with a high shear impeller. The resulting solution was cast on a PET release liner with a 1000 μm gap. Drying was done at 110°C in a static oven with ventilation. The dried films were evaluated for GSM and folding resistance. Formulation #1 and Formulation #2 produced low viscosity solutions that could not be cast properly. However, the resulting residue was in the form of a brittle film. This indicates that OSA starch is a film-forming polymer.

[0177] Preparation #3 was easy to prepare. Dissolving the OSA starch in water at 60°C was easy and foamy. The addition of CoQ10 to the solution was also smooth and the solution was easily homogenized with the Ultra-Turrax. The addition of alginate to the emulsion produced a very viscous solution that could not be mixed using a high shear impeller. Therefore, 200 gr of water had to be added to the solution to reduce the viscosity and mix properly. Casting was done on a PET release liner with a 1000 μm gap. Drying was done at 110°C (modified procedure) and 60°C (original procedure). The film obtained by drying at 110°C separated from the liner and multiple cracks formed. The film obtained by drying at 60°C formed more cracks than at 110°C. Neither the GSM nor the folding resistance could be measured for either film. The films were brittle and could not be handled.

[0178] Next, formulation #4 was modified by adding 100gr water (total 200gr) from the beginning to avoid the high viscosity observed in formulation 3. All steps of the process described in the previous formulation were good, emulsion and mixing were easily achieved. Casting was done on a release liner with a gap of 1000μm. Drying was done at 110°C and 60°C. Drying at 60°C required a very long time of 36 minutes. The resulting film peeled off from the liner and significant cracks formed. Both films had very poor mechanical properties, so GSM and folding endurance could not be measured.

Claims

1. 1. An orally administrable mucoadhesive film comprising at least one poorly water soluble bioactive material, at least one emulsifier, and an alginate as a major film forming polymer, the weight ratio between said bioactive material and said alginate being 1:2.5 to 2.5:1, the concentration of the emulsifier is less than 1 / 10 of the concentration of the bioactive material in the film; The emulsifier is a phospholipid.

2. The film of claim 1 , wherein the weight ratio between the bioactive material and the alginate is from 1:1 to 2.5:

1.

3. An orally administrable mucoadhesive film containing at least one poorly water-soluble bioactive material, at least one emulsifier, and an alginate as a major film-forming polymer, wherein the weight ratio between said bioactive material and said alginate is 1:2.5 to 2.5:1, the concentration of the emulsifier is less than 1 / 10 of the concentration of the bioactive material in the film; The film wherein the emulsifier is lecithin.

4. The film described in claim 3, wherein the weight ratio between the bioactive material and the alginate is 1:1 to 2.5:

1.

5. The film according to any one of claims 1 to 4, wherein the poorly water-soluble bioactive material has a water solubility of less than 10 mg / L at 20°C.

6. An orally administrable mucoadhesive film containing at least one poorly water-soluble bioactive material, at least one emulsifier, and an alginate as a major film-forming polymer, wherein the weight ratio between said bioactive material and said alginate is from 1:2.5 to 2.5:1, A film comprising as said bioactive material 15-45% by weight of the dry weight of said film of coenzyme Q10, and said emulsifier being lecithin.

7. 7. The film of claim 6, wherein the mucoadhesive film comprises 15 to 45% alginate by weight of the dry weight of the film, 15 to 45% coenzyme Q10 by weight of the dry weight of the film, and 0.05 to 5.0% lecithin by weight of the dry weight of the film, and optionally further comprises a plasticizer, a flavoring agent, and / or a filler.

Citation Information

Patent Citations

  • Film preparation

    JP2013249283A

  • Coenzyme q10 film formulation

    JP2018203618A

  • Sublingual and buccal film compositions

    US10285910B2

  • Oral dissolvable film that includes plant extract

    US20190269649A1

  • Film-shaped preparation comprising oily substances for oral administration

    US8758803B2